Isolation and characterisation of graves’ disease-specific extracellular vesicles from tissue maintained on a bespoke microfluidic device - Foster, Hayley; Wade, Mark; England, James; Greenman, John; Green, Victoria (Organs-on-a-Chip, 2021)
Abstract This report demonstrates the ability of a microfluidic device to maintain human Graves' disease tissue enabling the isolation and characterisation of Graves' disease specific exosomes. Graves' disease (n = 7) and non-Graves’ disease (Hashimoto's thyroiditis, n = 3; follicular adenoma, n = 1) human tissue was incubated in a microfluidic device for 6 days ± dexamethasone or methimazole and effluent was analysed for the size and concentration of extracellular vesicles (EV) using nanoparticle tracking analysis. Exosomes were isolated by centrifugation and characterised using Western blotting and qRT-PCR for miRNA-146a and miRNA-155, previously reported to be immunomodulatory. EV were detected in all effluent samples. No difference in concentration was observed in the EV released from Graves' compared to non-Graves’ disease tissue and although the size of EV from Graves' disease tissue was smaller compared to those from non-Graves’ disease tissue, the difference was not consistently significant. No effect of treatment was observed on the size or concentration of EV released. The exosome markers CD63 and CD81 were detectable in 2/5 Graves' disease tissue exosomes and CD63 was also evident in exosomes from a single non-Graves’ sample. miRNA-146a and miRNA-155 were detectable in all samples with no difference between tissue cohorts. Treatment did not influence miRNA expression in exosomes isolated from Graves' disease tissue. Although miRNA-146a and miRNA-155 were both elevated following treatment of non-Graves’ disease tissue with dexamethasone and methimazole, the increase was not significant. This study provides a proof of concept that incubation of tissue on a microfluidic device allows the detection, isolation and characterisation of extracellular vesicles from human tissue biopsies.
Keywords: Graves' disease; Microfluidics; Extracellular vesicles; Exosomes